Integrated primary care using a life course approach for prevention and control of non-communicable diseases: Indonesia’s perspective - Sutarsa, I Nyoman; Nopiyani, Ni Made Sri (Public Health and Preventive Medicine Archive, 2023)
An integrated primary care using a life course approach for preventing and controlling NCDs in Indonesia is the right policy decision. It strives to be holistic, addressing NCDs with a long-term vision across the critical stages where modifications can be made to minimise risks of developing NCDs. This policy direction is inherently complex mandating multi-sectoral and/or inter-sectoral approaches, as well as multi-disciplinary teams. Additionally, existing evidence suggests the intricate connections between health, social, economic, and environmental across the lifespan7. Taking a life course approach also means the governments must extend the NCD prevention and control measures beyond health sector alone. This means that effective implementation of an integrated primary care using a life course approach require long-term strategies to strengthening multi-sectoral partnerships to promote a life course approach across all government sectors and community systems.